Temporal shaping of high‐voltage picosecond electric pulses for electronic spectroscopy and bioelectric applications. Issue 2 (26th November 2022) - Wehbi, Sahar; Tabcheh, Nour; Tonello, Alessandro; Orlacchio, Rosa; Leveque, Philippe; Arnaud‐Cormos, Delia; Mansuryan, Tigran; Fabert, Marc; Tantot, Olivier; Vergnole, Sebastien; Couderc, Vincent
Abstract: In this paper, we present the temporal and spectral shaping of kilovolt picosecond electrical pulses obtained by using the linear switching process with femtosecond laser source. The frozen wave generator integrating up to four photoconductive semiconductor switches is activated by varying the optical pulse amplitude and time delay. Electric pulses with rise time and duration as short as 60 and 100 ps, respectively are used to implement a microwave spectroscopy experiment. This optoelectronic device is synchronous with the optical pulses which can be used for optical spectroscopy, after nonlinear frequency conversion. This single‐shot microwave spectroscopy technique was used to characterize the resonances of a passive dielectric resonator. Pulse shaping integrating coherent wave combining is also demonstrated.